Nicotinic acetylcholine receptor dysfunction in addiction and in some neurodegenerative and neuropsychiatric diseases - Vallés, Ana Sofía (2023)
Fil: Vallés, Ana Sofía. Universidad Nacional del Sur. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Bioquímicas de Bahía Blanca; Argentina